2018
DOI: 10.37358/mp.18.1.4973
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Graphene Oxide and Graphite on Dry Sliding Wear Behavior of Polyester Composites

Abstract: Graphene oxide and graphite filled polyester composites were prepared by using conventional melt-mixing methods in order to improve tribological performance of polyester. It was investigated friction stability, microhardness, friction coefficient, and specific wear rate of the composites in details. It was found that the presence of graphite and graphene oxide influenced friction coefficient and wear rate of the composites. Graphene oxide decreased wear rate with increasing of test speed and graphite decreased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…The PTFE material + 15% fiberglass compared to the other materials analyzed has a lower wear rate. Figure 7 shows microscopic images [19] of the contact area in the sliding direction (from left to right) for the improved PTFE structure for different operating conditions [15,19] The results obtained experimentally correspond to many researchers found in specialized journals [1,2,7,8,[10][11][12][13][14]20].…”
Section: Resultsmentioning
confidence: 53%
“…The PTFE material + 15% fiberglass compared to the other materials analyzed has a lower wear rate. Figure 7 shows microscopic images [19] of the contact area in the sliding direction (from left to right) for the improved PTFE structure for different operating conditions [15,19] The results obtained experimentally correspond to many researchers found in specialized journals [1,2,7,8,[10][11][12][13][14]20].…”
Section: Resultsmentioning
confidence: 53%
“…An effective repairing method of steel surface is applying coatings with high toughness, anti-friction, and anti-wear to protect the steel from the attack of the service environment. [7][8][9][10] Therefore, there is an urgent need to develop the polymeric wear-resistant coating that can be used for surface restoration and has high toughness.…”
Section: Introductionmentioning
confidence: 99%
“…Steel has a fatal flaw of being vulnerable to wear and corrosion, and thus may fail to meet the safety requirements in the aggressive environments. An effective repairing method of steel surface is applying coatings with high toughness, anti‐friction, and anti‐wear to protect the steel from the attack of the service environment 7–10 . Therefore, there is an urgent need to develop the polymeric wear‐resistant coating that can be used for surface restoration and has high toughness.…”
Section: Introductionmentioning
confidence: 99%
“…They have indicated that they have an important influence on the friction and abrasion properties of the resulting transfer film layer. Bastiurea et al [12] prepared the graphene oxide and graphite filled polyester composites by using conventional melt-mixing methods to improve the tribological performance of polyester. Hassan et al [13] investigated the tribological properties of unfilled Low-Density Polyethylene (LDPE), Polyamide-12 (PA-12), and graphene nanoplatelets (GNPs) filled polymers by a pin-on-disc tester.…”
Section: Introductionmentioning
confidence: 99%